A functional BCI model by the P2731 working group: control interface. Issue 4 (2nd October 2021) - Easttom, Chuck; Bianchi, Luigi; Valeriani, Davide; Nam, Chang S.; Hossaini, Ali; Zapała, Dariusz; Roman-Gonzalez, Avid; Singh, Avinash K; Antonietti, Alberto; Sahonero-Alvarez, Guillermo; Balachandran, Pradeep
ABSTRACT: In order to facilitate communication and collaboration between researchers, Brain–computer interfaces (BCI) require a generally applicable functional model as well as a common vocabulary. The IEEE P2731 working group is in the process of developing such a functional model and a lexicon of BCI terminology. Such a functional model has multiple aspects including the control interface, physiology, transducers, etc. This current paper focuses on the control interface aspects of that model. Having a generally applicable control interface model will facilitate interdisciplinar y research and communication. The control interface is a critical part of the functional model and is described in this current paper. The control interface presented intentionally is intentionally kept general in order to be widely applicable. Some details are specific to a particular application and are thus left to those applications. It does contain the encoder (which also contains a decoder), with a feedback submodule.